Analisis Yuridis Perkawinan Beda Agama dengan Pendekatan Maqashid Al-Syariah dalam Konteks Negara Hukum Pancasila - Budiarti Budiarti (Justicia Islamica, 2018)
This article explores the juridical analysis of interfaith marriage with the maqashid al-syari'ah approach in the context of the Pancasila of the rule of law. The results of the study confirm that the value of maqashid al-syari'ah animates the substance of Undang-Undang No. 1 Tahun 1974 of Marriage. Juridical products on marriage by making religion a legal requirement of marriage and the legitimacy of the state through administrative action are not discriminatory actions and do not violate the basic rights of citizens. Even affirming the functional relationship between religion and the state in the context Pancasila of the rule of law. As well, in the views of religious assemblies, namely MUI, PGI, KWI, WALUBI, PHDI, and MATAKIN. The religious assemblies are of the view, interfaith marriage is not an ideal marriage according to the teachings of each religion. The implication of this study is that it is necessary to pay attention to religious values in formulating a juridical product towards a responsive legal product. In addition, it is necessary to take preventive measures and advocate for the community early so that there will no longer be interfaith marriages in order to realize legal certainty for couples who have carried out marriage.Artikel ini mengeksplorasi tentang analisis yuridis perkawinan beda agama dengan pendekatan maqashid al-syari’ah dalam konteks negara hukum Pancasila. Hasil kajian menegaskan bahwa nilai maqashid al-syari’ahmenjiwai substansi Undang-Undang No. 1 Tahun 1974 tentang Perkawinan. Produk yuridis tentang perkawinan dengan menjadikan agama sebagai syarat sahnya perkawinan serta legitimasi negara melalui tindakan administratif, bukanlah tindakan diskriminatif dan tidak melanggar hak-hak dasar warga negara. Bahkan mengukuhkan relasi fungsional antara agama dan negaradalam konteks negara hukum Pancasila. Demikian pula dalam pandangan majelis-majelis agama, yaitu MUI, PGI, KWI, WALUBI, PHDI, dan MATAKIN. Majelis-majelis agama tersebut berpandangan, perkawinan beda agama bukanlah perkawinan yang ideal menurut ajaran masing-masing agama. Implikasi dari kajian ini bahwa perlu memerhatikan nilai-nilai agama dalam merumuskan suatu produk yuridis menuju suatu produk hukum responsif. Selain itu, perlu upaya preventif dan mengadvokasi masyarakat secara dini agar tidak lagi terjadi perkawinan beda agama demi mewujudkan kepastian hukum bagi pasangan yang telah melaksanakan perkawinan.